The effect of feeding frequency on insulin and ghrelin responses in human subjects - Solomon, Thomas P. J.; Chambers, Edward S.; Jeukendrup, Asker E.; Toogood, Andrew A.; Blannin, Andrew K. (British journal of nutrition, 2008)
Recent work shows that increased meal frequency reduces ghrelin responses in sheep. Human research suggests there is an interaction between insulin and ghrelin. The effect of meal frequency on this interaction is unknown. Therefore, we investigated the effect of feeding frequency on insulin and ghrelin responses in human subjects. Five healthy male volunteers were recruited from the general population: age 24 (sem 2) years, body mass 75·7 (sem 3·2) kg and BMI 23·8 (sem 0·8) kg/m2. Volunteers underwent three 8-h feeding regimens: fasting (FAST); low-frequency (two) meal ingestion (LOFREQMEAL); high-frequency (twelve) meal ingestion (HIFREQMEAL). Meals were equi-energetic within trials, consisting of 64 % carbohydrate, 23 % fat and 13 % protein. Total energy intake was equal between feeding trials. Total area under the curve for serum insulin and plasma ghrelin responses did not differ between trials (P>0·05), although the hormonal response patterns to the two meal feeding regimens were different. An inverse relationship was found between serum insulin and plasma ghrelin during the FAST and LOFREQMEAL trials (P < 0·05); and, in the postprandial period, there was a time delay between insulin responses and successive ghrelin responses. This relationship was not observed during the HIFREQMEAL trial (P>0·05). This study provides further evidence that the postprandial fall in ghrelin might be due, at least partially, to the rise in insulin and that high-frequency feeding may disrupt this relationship.